Implementation of Aes Algorithm with Data Encryption on Student Attendance for Information Security at One of The Vocational High Schools in Bandung - Ika Tariska; Rohmat Nur Ibrahim; Dani Rohpandi; Eti Rahmawati (Majalah Bisnis & IPTEK, 2026)
This study addresses the vulnerabilities of digital attendance systems in educational institutions, particularly regarding data security. Many existing systems allow unauthorized access and manipulation due to inadequate security measures. The objective of this research is to enhance data security in the student attendance system at a vocational high school in Bandung by implementing the Advanced Encryption Standard (AES-256) algorithm. Utilizing the Waterfall methodology, the study follows a structured approach through the phases of analysis, design, implementation, and testing. Sensitive data, such as student identification numbers and attendance records, are encrypted using the AES algorithm before being stored in the database. The results reveal that the encrypted data remains secure as ciphertext and is inaccessible without the appropriate decryption key. Importantly, the implementation of the encryption does not compromise the system's performance. Overall, this study contributes valuable insights into enhancing data security measures for digital attendance systems, offering a robust solution that protects sensitive information while maintaining functionality.